Exploring the Value of the Capability Approach for Vocational Education and Training Evaluation: Reflections from South Africa - Lesley Powell; Simon McGrath (Revue Internationale de Politique de Développement)
In the late 1990s, South Africa faced the three-fold challenge of reforming the apartheid-divided institutional landscape of vocational education and training (VET) institutions; ensuring equitable access to skills; and reorienting its skills development system in line with the nation’s reinsertion into the global economy. A wave of institutional reforms was enacted which was followed by a large programme of evaluative research. While this body of work was both valuable and necessary, it nonetheless had several limitations. As part of efforts to overcome these, the authors suggest an alternative evaluation method that draws on insights from the ‘capability approach’. By putting the needs of people first – rather than the needs of the economy – the capability approach emphasises social justice, human rights and poverty alleviation in VET evaluation. This approach is more focused on the values and goals of individuals and institutions, while retaining the economic rationale as a key analytical tool and emphasising the continued importance of evaluation for the improvement of delivery and outcomes.